Applications Of Biotechnology To Crops: Benefits And Risks - Persley, Gabrielle J.; Siedow, James N. (Council for Agricultural Science and Technology (CAST), 1999)
This issue paper is a summary of the recent scientific developments that underpin modern biotechnology and a discussion of the potential risks and benefits when these are applied to agricultural crops. This introductory paper is intended for a general audience. Released at the Third Ministerial Conference of the World Trade Organization in Seattle, December 2, 1999.